The intensive margin puzzle and labor market adjustment costs - Dennis Wesselbaum (Kiel Institute for the World Economy (IfW), 2011)
This paper documents a puzzling fact, namely that there is a significant negative relation between employment protection legislation and the usage of the intensive margin of labor market adjustments. We then make use of a Real Business Cycle model and introduce search and matching frictions as well as adjustment costs along the extensive and the intensive labor market margins. We show that the model is able to replicate the observed pattern, if we assume low firing costs and relatively large hours adjustment costs. Furthermore, the model requires those values to replicate the U.S. business cycle statistics.
Keywords: C10; E32; J41; 330; Adjustment Costs; Extensive Margin; Intensive Margin; Kündigungsschutz; Arbeitsmarkt; Anpassungskosten; Arbeitszeit; Real Business Cycle; Theorie; USA